The Influence of Vegetation on the Oviposition of Mosquitoes in Cans Filled With Water of Varying Salinities - Barquilla, Manuel (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
A set-up of 24 cans each containing 250 ml water of varying salinities ranging 0 ppt (rainwater) to 35 ppt (seawater) were randomly arranged in three rows and housed under a plastic roofing in shaded area, heavily populated with banana trees and in open, sunlit area in two localities-Station I (Luinab, Iligan City), located 2.5 kilometers from the seashore, and Station II (Canaway & Saray, Iligan City), a coastal area located 25 meters from the seashores. Aedes spp larvae were collected from cans with 0 ppt and 5 ppt in the shaded area in Station I (Luinab) and Station II (Canaway,). Mansonia ssp. larvae were also collected in cans with 5 ppt under shade in Station II (Canaway). No larvae were found in all cans in the area and in cans with 10 ppt, 15 ppt 20 ppt, 25 ppt, 30 ppt and 35 ppt in the shaded areas in both localities.